Various Manifestations of Phonetic Interference - Namozova Dilnoza Berdimurotovna (International Journal on Integrated Education, 2022)
The article examines the violation of the language norm that manifests itself in foreign language speech at all levels. At the same time, researchers as the most significant recognize negative phonetic interference. A foreign accent, as a direct result of interference, the signs and effects of which have not yet been sufficiently studied, plays an important and often underestimated role in oral intercultural communication.